Biosimilars in Germany: the emergence of a new industry in the light of the varieties of capitalism approach. Issue 3 (16th March 2017) - Pyka, Andreas; Buchmann, Tobias; Vermeulen, Ben
ABSTRACT: Although lagging behind the USA in biologics, German firms are forging ahead in the emerging field of biosimilars. This development confirms earlier explanations of the differences in these industries given by the Varieties of Capitalism approach. With the recent differentiation in biopharmaceuticals, again, the differences in the institutional environment on both sides of the Atlantic are responsible for different dynamics. However, this time German companies are in the better position: the industry refers to a tradition of engineering capabilities in chemicals and pharmaceuticals. Additionally, European regulation introduced the world's first regulatory framework, which moreover is designed in a progressive way concerning market admission.